Quantum oscillations as the tool for study of new functional materials (Review Article) - Gusynin, V.P.; Loktev, V.M.; Luk’yanchuk, I.A.; Sharapov, S.G.; Varlamov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
We present an overview of our recent results on quantum magnetic oscillations in new functional materials. We begin with the Lifshitz and Kosevich approach for quasi-2D layered materials and obtain general formulas for the oscillatory parts of the grand thermodynamic potential and magnetization. Then we consider the oscillations of the Nernst–Ettingshausen coefficient which consists of thermal and magnetization parts. The difference between normal and Dirac carriers is also discussed. To conclude we consider a model for multilayer graphene which allows to calculate exactly the Berry phase which remains undetermined in the Lifshitz–Kosevich approach. The magnetic oscillations of the density of states and capacitance for different number of the carbon layers are described.